The Impact of Changes in InFeed Rate on Surface Integrity after Chrome Plate Grinding by Microcrystalline Corundum - Marek, Martin; Novák, Martin; Šramhauser, Karel (Manufacturing Technology Journal, 2019)
The efficient processing of materials, the development of machine concepts and grinding tools, as well as growing environmental and economic pressure are existing challenges in grinding. Chromium coatings are mainly used for components where corrosion protection is required, but also for the repair of worn parts. This paper presents and discusses the possibilities of utilizing changes in feed rate to achieve guaranteed surface integrity, which is very important for the life of the component. The results are presented in the form of tables and graphs, where I focus mainly on parameters of surface roughness and circularity.
Keywords: grinding; surface integrity; cutting conditions; hard chrome coating